Psychology made visual: the sandman overture by Neil Gaiman, J. H. Williams III and Dave Stewart. Issue 2 (3rd April 2018) - Hume, Kathryn
Abstract: Scott McCloud and Will Eisner based their foundational studies of graphic narrative aesthetics on black and white line drawing. Much of what provides character psychology in Gaiman's The Sandman Overture, however, is the color and the nature of the shading, the different styles of drawing, the shapes of panels, and the palette chosen for scenes. I would like to show how Gaiman, Williams, and Stewart project the psychology of Dream and of other characters through scenery, through character portraits against typifying backgrounds, through visualization of the self as multiple, through panel shapes, and through symbolism. Williams and Stewart use their art to show us Dream's fears and shortcomings and mental patterns and explain much that was not explicit in The Sandman . Thanks to the overwhelmingly dense and rich artwork of this collaboration with Gaiman, we get separate but consilient views of the characters through actions, words, and pictures.